(untitled) (Papeles, 2022)
The declaration of a territory as a Wetland of International Importance enables the development of various plans and programs at different scales in order to ensure the wise use of the wetland (art. 3, Convention on Wetlands of International Importance especially as Waterfowl Habitat). Among them, in 2019 the Management Plan for the Ramsar Site Delta del Paraná was presented, prepared with the participation of the provinces of Entre Ríos, Santa Fe, the national government, experts, academics and inhabitants. In addition, the two national parks included in the site seek to articulate their management and operational plans with this plan. In 2021, based on fieldwork (dato omitido para salvaguardar autoría), in the town of Las Cuevas, Entre Ríos. Within this framework, we found that the development of ecotourism encompasses a set of activities that are regulated by different regulations, at different state levels and that respond to different principles. In this paper we propose to present the regulations of the activities related to ecotourism in the locality and to consider the relationships and intersections between them.